2005
DOI: 10.1161/01.res.0000185322.46009.f5
|View full text |Cite|
|
Sign up to set email alerts
|

cAbl Tyrosine Kinase Mediates Reactive Oxygen Species– and Caveolin-Dependent AT 1 Receptor Signaling in Vascular Smooth Muscle

Abstract: Abstract-Important output signals of the angiotensin subtype 1 receptor (AT 1 R) in vascular smooth muscle cells (VSMCs) are mediated by angiotensin II (Ang II)-stimulated transactivation of the epidermal growth factor receptor (EGF-R), which is critical for vascular hypertrophy. Ang II-induced EGF-R transactivation is mediated through cSrc, a proximal target of reactive oxygen species (ROS) derived from NAD(P)H oxidase (NOX) and is dependent on AT 1 R trafficking through caveolin1 (Cav1)-enriched lipid raft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
77
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 47 publications
4
77
0
1
Order By: Relevance
“…In VSM, Cav-1 plays a role in the coupling of ␣-adrenergic, ANG II, and endothelin receptors to VSM contraction and growth (34,38,39,43). In the endothelium, Cav-1 anchors eNOS to caveolae, thus preventing its activation and reducing NO production and vascular relaxation (3,7,33).…”
Section: Discussionmentioning
confidence: 99%
“…In VSM, Cav-1 plays a role in the coupling of ␣-adrenergic, ANG II, and endothelin receptors to VSM contraction and growth (34,38,39,43). In the endothelium, Cav-1 anchors eNOS to caveolae, thus preventing its activation and reducing NO production and vascular relaxation (3,7,33).…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition to these second messengers and ADAM17, multiple upstream components have been reported to participate in EGFR transactivation by Ang II. 2,6,7,26 However, the relationships between these distinct signal transduction components still remain unclear. Because ADAM phosphorylation 27,28 seems to be required for the activation of certain ADAM, it is possible that the upstream components may converge on an ADAM kinase that regulates ADAM17 activity.…”
Section: Ohtsu Et Al Adam17 Mediates Vascular Hypertrophy By Angiotenmentioning
confidence: 99%
“…2,4 Intracellular Ca 2ϩ elevation, protein kinase C activation or reactive oxygen species (ROS) production seems to be required for the upstream of EGFR transactivation induced by Ang II through the AT 1 receptor. [5][6][7] Recently, the mechanism of EGFR transactivation via several GPCRs has been shown to involve a proteolytic cleavage ("ecto-domain shedding") of a membrane-anchored EGF ligand precursor to release a biologically active growth factor mediated through ADAM (a disintegrin and metalloprotease) family metalloproteases. 8,9 Previously, we and others have shown that heparin-binding EGF (HB-EGF) shedding is essential for EGFR transactivation via the AT 1 receptor.…”
mentioning
confidence: 99%
“…8,9 These results are consistent with a model that requires temporal dispersion and organization of the AT 1 R signaling repertoire in VSMCs. 7,10 Accumulating evidence suggests that receptors and the signaling molecules with which they associate are not randomly distributed in the cell membrane but are localized in specialized signaling domains. Functionally distinct microdomains, formed by the lateral packing of glycosphingolipids and cholesterol within the membrane bilayer, have been identified in plasma membranes.…”
mentioning
confidence: 99%
“…7,10,12,13 The full expression of the AT 1 R signaling repertoire depends on caveolae/lipid rafts and reactive oxygen species (ROS) production by reduced nicotinamideadenine dinucleotide phosphate (NADPH) oxidase. 7,10,13,14 Several recent reviews have described the physiological and pathophysiological roles of caveolae and caveolins in the cardiovascular system generally. [15][16][17][18] The main focus of this review is to summarize the recent progress on the emerging understanding of the role of Cav1 as a central organizer for the spatially and temporally regulated, ROS-dependent, growth-related AT 1 R signaling in VSMCs.…”
mentioning
confidence: 99%